2019
DOI: 10.1108/gkmc-03-2019-0033
|View full text |Cite
|
Sign up to set email alerts
|

Citizens’ assessment of the information quality of e-government websites in Pakistan

Abstract: Purpose E-government websites/portals are effective modes of communication between governments and citizens. The information quality (IQ) of these websites/portals is of vital importance and, hence, is worth assessing, to ensure their effectiveness. This study aims to assess the IQ dimensions of e-government websites/portals in Pakistan and also evaluate the most significant IQ indicators. Design/methodology/approach This study used a quantitative research method based on a survey. The data were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 39 publications
3
17
0
2
Order By: Relevance
“…In the instance of citizens using local government websites for public services in Indonesia, this study also justified that information quality influences trust in e-government (p-value=0.001). As a result, this research validates the establishment of some scholars in other countries (Khan et al, 2021;Losanta & Deshmukh, 2019;Aljazzaf, 2019;Nofal et al, 2021;Kaushik & Mishra, 2019;Abu Shanab, 2019;Rasool et al, 2019;Putri & Ruldeviyani, 2019;Lee et al, 2019).…”
Section: Figure 2 Validated Research Modelsupporting
confidence: 85%
See 1 more Smart Citation
“…In the instance of citizens using local government websites for public services in Indonesia, this study also justified that information quality influences trust in e-government (p-value=0.001). As a result, this research validates the establishment of some scholars in other countries (Khan et al, 2021;Losanta & Deshmukh, 2019;Aljazzaf, 2019;Nofal et al, 2021;Kaushik & Mishra, 2019;Abu Shanab, 2019;Rasool et al, 2019;Putri & Ruldeviyani, 2019;Lee et al, 2019).…”
Section: Figure 2 Validated Research Modelsupporting
confidence: 85%
“…Abu-Shanab also showed information quality as predictor variable of trust in e-government as dependent variable (Abu Shanab, 2019). Furthermore Rasool et al assessed that the information quality of websites/portals is vital importance of citizens' use of e-government in Pakistan (Rasool et al, 2019). The National Public Procurement Agency (NPPA) at Indonesian Government Agencies uses the website as a service to citizens to share information related to regulations, organizational profiles, and functions.…”
Section: Information Quality and Trust In E-governmentmentioning
confidence: 99%
“…According to [17], effort expectancy (EE) is "the degree of ease associated with the use of the system". Several studies, such as [6,10,18] found that the easier a technology is Performance Expectancy (PE) is defined as: "the degree to which using a technology will provide benefits in performing certain activities" [17]. Ref.…”
Section: H1 Performance Expectancy (Pe) Has a Positive Influence Rela...mentioning
confidence: 99%
“…According to [17], effort expectancy (EE) is "the degree of ease associated with the use of the system". Several studies, such as [6,10,18] found that the easier a technology is to use, the more likely users are to adopt it, also stated that Individuals often believed that they would receive help from using user-friendly technologies. Camilleri [2] and Mensah et al [25] stated that effort expectancy is an important predictor and has a direct and significant effect on the citizens' intention to adopt and use e-government services.…”
Section: H1 Performance Expectancy (Pe) Has a Positive Influence Rela...mentioning
confidence: 99%
See 1 more Smart Citation